2005
DOI: 10.1101/lm.92505
|View full text |Cite
|
Sign up to set email alerts
|

Recollection in an episodic-like memory task in the rat

Abstract: Episodic memory in humans is the conscious recollection of a past event. Animal models of episodic-like memory assess the memory for “what” happened, “where” it happened, and either “when” it happened, or in “which” context it happened, although recollection on such tasks is often difficult to measure. Here we present the first evidence of successful recollection of a past event in a rat in a task which is easily performed, requires little training, and is easily adaptable for other commonly used laboratory sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 25 publications
2
99
0
Order By: Relevance
“…Critically, an animal that uses judgments of relative familiarity need not retrieve an episodic memory of the earlier event (see details that follow). Other approaches have sought to document that animals can discriminate: combinations of item-place-context (Eacott & Norman, 2004;Kart-Teke, De Souza Silva, Huston, & Dere, 2006), the sequential order in which events (e.g., odors, objects) are presented (Dere, Huston, & De Souza Silva, 2005a, 2005bEacott, Easton, & Zinkivskay, 2005;Ergorul & Eichenbaum, 2004;Fortin, Wright, & Eichenbaum, 2004;Hunsaker, Lee, & Kesner, 2008;Kart-Teke et al, 2006;Kesner & Hunsaker, 2010;Kesner, Hunsaker, & Warthen, 2008), trial-by-trial records of information (Devkar & Wright, 2016;Kheifets, Freestone, & Gallistel, 2017;Wright, 2007), and the elements of configural learning (Iordanova, Burnett, Aggleton, Good, & Honey, 2009;Iordanova, Burnett, Good, & Honey, 2011;Iordanova, Good, & Honey, 2008). For related reviews, see Dere, Dere, De Souza Silva, Huston, and Zlomuzica (2017) and Eacott and Easton (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Critically, an animal that uses judgments of relative familiarity need not retrieve an episodic memory of the earlier event (see details that follow). Other approaches have sought to document that animals can discriminate: combinations of item-place-context (Eacott & Norman, 2004;Kart-Teke, De Souza Silva, Huston, & Dere, 2006), the sequential order in which events (e.g., odors, objects) are presented (Dere, Huston, & De Souza Silva, 2005a, 2005bEacott, Easton, & Zinkivskay, 2005;Ergorul & Eichenbaum, 2004;Fortin, Wright, & Eichenbaum, 2004;Hunsaker, Lee, & Kesner, 2008;Kart-Teke et al, 2006;Kesner & Hunsaker, 2010;Kesner, Hunsaker, & Warthen, 2008), trial-by-trial records of information (Devkar & Wright, 2016;Kheifets, Freestone, & Gallistel, 2017;Wright, 2007), and the elements of configural learning (Iordanova, Burnett, Aggleton, Good, & Honey, 2009;Iordanova, Burnett, Good, & Honey, 2011;Iordanova, Good, & Honey, 2008). For related reviews, see Dere, Dere, De Souza Silva, Huston, and Zlomuzica (2017) and Eacott and Easton (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is now considerable evidence that a range of animals have episodic-like memory, including rats (Babb & Crystal, 2005), magpies (Zinkivskay et al, 2009), chickadees (Feeney et al, 2009), and meadow voles (Ferkin et al, 2008), issues over designing an appropriate experiment continue to plague this field. The most systematic difficulty concerns the 'when' component, with differing groups defining this in different ways (e.g., including a place in a sequence: Ergorul & Eichenbaum, 2004; a time of day: Zhou & Crystal, 2009; and using "which" instead of "when": Eacott, Easton, Zinkivskay, 2005;Eacott & Norman, 2004). Common to all of these approaches, however, is that the test would allow animals to demonstrate their ability to remember what, where and when in combination.…”
Section: Figure 3 Photographs Showing the Elevated Feeder (To Deter mentioning
confidence: 99%
“…In the animal literature, research on memory for past events has shown that information present at the time of encoding can be an effective cue at retrieval (Clayton & Dickinson, 1998;Eacott, Easton, & Zinkivskay, 2005;Martin-Ordas, Berntsen, & Call, 2013;Mendes & Call, 2014). For instance, Eacott et al (2005) showed that rats could use a contextual feature that was present at encoding and retrieval to successfully locate a desired object.…”
mentioning
confidence: 99%